Practical Learning Media in Subject Maintenance of Chassis and Power (MCP) Based Online: Simple Learning Using Videos on YouTube - Rabiman, Rabiman; Sudira, Putu; Sofyan, Herminarto; Nurtanto, Muhammad (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Online media-assisted learning is becoming a necessity at this time, where users have a level of interest in using mobile devices. YouTube has been used by several universities as a learning medium that complements conceptual understanding. This study develops learning media in the curriculum of maintenance of chassis and power (MCP) and measures the perspective of students after online-based MCP media is applied. Researchers involved material experts, media experts, and expert practitioners in improving the quality of MCP media and involved 163 respondents as users to assess the feasibility of MCP media, thus determining the media to use YouTube is acceptable. The results confirm that all aspects of material understanding, language use, benefits and graphics on MCP media are recommended according to YouTube usage. Researchers summarize that the online media "YouTube" is effective as a learning methodology and relevant to user needs. The involvement of experts is important in the acceptance and suitability of quality media. It is recommended that practical or abstract competencies can be mastered easily using online media, YouTube.